Pelatihan Pembuatan Nata de Coco di Kampung Sumber Rejeki Distrik Kurik Kabupaten Merauke - Mega Ayu Yusuf; Sadrack L Pagiling; Jamaludin Jamaludin; Yosefina Mangera; Yus Witdarko; Suryadi Suryadi (Jurnal Pengabdian Masyarakat IPTEKS, 2024)
Sumber Rejeki Village is one of the areas that produces coconut as a plantation product. Much coconut water from the copra factory in Sumber Rejeki Village is still wasted as waste. Coconut water mainly contains glucose, fat and other nutrients. The presence of these nutritional ingredients can be used as a growth medium for microorganisms, including Acetobacter xylinum. This bacteria uses the ingredients in coconut water to convert it into nata de coco. PKK women in Sumber Rejeki Village do not yet know the steps for making it, therefore they need to be trained on how to make nata de coco. The training method involves: 1) presenting material about nata de coco and how to make nata de coco; 2) Demonstration of making nata de coco; and 3) PKK women make nata de coco guided by the service team. The results of the training showed that 1) PKK women understand the process or how to make nata de coco from coconut water, 2) PKK women can make their own nata de coco from coconut water using simple equipment.